Pemanfaatan Chromebook dengan Model Project Based Learning Terintegrasi Tri-N Pada Pendidikan Pancasila Sekolah Dasar - Rahmawati, Arini; Wibawa, Sutrisna (Jurnal Kewarganegaraan, 2024)
AbstractEducation is an effort to foster and develop human personality spiritually and physically. This study aims to assess the efficiency of employing Chromebooks with the Project-Based Learning model integrated with Tri N Teachings while examining the challenges faced and initiatives taken in Civic Education for fourth-grade elementary school students. This research adopts a descriptive qualitative approach and involves teachers and students from Class IV at Pakem Kalasan State Elementary School in Sleman Regency. Data collection encompasses interviews, observations, and documentation. Based on the research results, it can be seen that 1) learning activities that utilize Chromebooks in integrated PjBL model Pendidikan Pancasila Learning with Tri N Teachings in Class IV of Pakem Kalasan Elementary School, Sleman Regency provide deeper understanding and experience and foster creativity in students, 2) obstacles in carrying out activities learning that utilizes Chromebooks in integrated PjBL model PKN Learning Tri N Teachings, namely the lack of teacher knowledge in utilizing Chromebooks that are available in educational units as well as the lack of teachers in implementing innovative learning models in the classroom, and 3) Efforts have been undertaken through the organization of In-House Training (IHT) sessions for teachers with the aim of enhancing their competence in effectively utilizing and implementing diverse and innovative teaching methods within the classroom.-------------Abstrak Pendidikan adalah usaha membina dan mengembangkan kepribadian manusia baik dibagian rohani atau dibagian jasmani. Tujuan penelitian ini adalah untuk mengetahui efektivitas pemanfaatan chromebook dengan model Project Based Learning terintegrasi Ajaran Tri N, hambatan dan usaha yang dilakukan pada mata pelajaran Pendidikan Pancasila di Kelas IV siswa Sekolah Dasar. Penelitian ini merupakan penelitian kualitatif deskriptif. Subjek penelitian adalah guru dan siswa kelas IV Sekolah Dasar Negeri Pakem Kalasan Kabupaten Sleman. Teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Berdasarkan hasil penelitian dapat dilihat bahwa 1) aktivitas pembelajaran yang memanfaatkan Chromebook pada Pembelajaran Pancasila model PjBL terintegrasi Ajaran Tri N di Kelas IV SD Negeri Pakem Kalasan Kabupaten Sleman memberikan pemahaman dan pengalaman yang lebih mendalam serta menumbuhkan kreativitas pada siswa, 2) hambatan dalam melaksanakan kegiatan pembelajaran yang memanfaatkan Chromebook pada Pembelajaran Pendidikan Pancasila model PjBL terintegrasi Ajaran Tri N yaitu  kurangnya pengetahuan guru dalam memanfaatkan chromebook yang telah tersedia di satuan pendidikan serta kurangnya guru dalam menerapkan model pembelajaran inovatif di dalam kelas, dan 3) usaha yang dilakukan adalah dengan mengadakan IHT (In House Training) kepada guru guna meningkatkan kompetensi dalam memanfaatkan dan menerapkan pembelajaran inovatif dan bervariatif di dalam kelas.